Enhancement of reflected waves in single-hole polarimetric borehole radar measurement. - Miwa, T.
A polarimetric approach is presented to extract information of reflected waves that is masked by the transmitter-receiver directly coupled wave in a single-hole borehole radar measurement. Radar polarimetry theory is expanded to an omnidirectional radar system with electric and magnetic dipoles arranged on the same axis. First, we formulate the transfer functions directly coupled between the antennas for cross-hole and single-hole arrangements in copolarized channels. We found that the theoretical scattering matrices of the direct-wave coupling is identical to the scattering matrix from a dihedral corner reflector. Second, we also consider signals in polarimetric channel of a wave reflected from a plane scatter in single-hole arrangements. As advanced reflection borehole radar measurement, we demonstrate a technique for both reduction of the directly coupled wave and enhancement of the reflected waves from a plane fracture with measured data in dipole-dipole and slot-slot antenna combinations. For quantitative determination of the scattering matrix, we use a technique to compensate the antenna transfer functions by the time derivative of the directly coupled signals in single-hole measurement. Also, we propose a technique to reduce the directly coupled component by adding vertical (VV) and horizontal (HH) signals and we showed that the directly coupled wave is effectively reduced and reflected waves are enhanced with experimental data. Finally, we show that this technique is more useful for near-range reflector detection than a conventional subtraction technique with moving average of the measured waveforms
Keywords: Antenna transfer functions; Copolarized channels; Cross-hole arrangement; Dihedral corner reflector; Dipole-dipole antenna; Direct-wave coupling; Directly coupled signals; Electric dipoles; Experimental data; Horizontal signals; Magnetic dipoles; Measured data; Near-range reflector detection; Omnidirectional radar system; Plane fracture; Plane scatter; Polarimetric channel; Radar polarimetry theory; Reflected waves enhancement; Reflection borehole radar measurement; Scattering matrices; Single-hole polarimetric borehole radar measurement; Slot-slot antenna; Time derivative; Transmitter-receiver directly coupled wave; Vertical signals